Oxidative stress and psoriasis: the effect of antitumour necrosis factor‐α inhibitor treatment. (25th April 2013) - Bacchetti, T.; Campanati, A.; Ferretti, G.; Simonetti, O.; Liberati, G.; Offidani, A.M.
Summary: Background Psoriasis is a chronic, inflammatory skin condition associated with a high frequency of cardiovascular events. Modifications of plasma lipids, and an increase in the levels of biochemical markers of inflammation and lipid peroxidation have been reported in subjects with psoriasis, suggesting a relationship between psoriasis, inflammation and oxidative damage. Objectives To investigate whether modulation of inflammatory activity by tumour necrosis factor‐α inhibitors in patients with psoriasis is associated with modification of lipid profiles, oxidative stress and paraoxonase (PON)1 activity. Methods The levels of plasma lipids and lipoprotein(a), and the levels of the markers of inflammation and lipid peroxidation were evaluated in subjects with psoriasis ( n = 23) before and after 24 weeks of treatment with etanercept. In the same subjects plasma total antioxidant capacity and the activity of PON1, an antioxidant and anti‐inflammatory enzyme associated with the high‐density lipoproteins (HDLs), were investigated. Results The results showed that clinical improvement in patients with psoriasis treated with etanercept is associated with a reduction in the levels of inflammatory markers [C‐reactive protein (CRP)] and lipid peroxidation, and also with increased antioxidant capacity in the serum of patients with psoriasis. These modifications are associated with a significant increase in the activity of PON1. A significant increase in the PON1/CRP ratio has also been observed in patients with psoriasis after treatment. The significant inverse correlation between CRP and PON1 activity suggests a relationship between PON1 activity and inflammation. Conclusions Treatment with etanercept is associated with a reduction in lipid peroxidation and an improvement in HDL antioxidant and anti‐inflammatory properties. Abstract : What's already known about this topic? Psoriasis is associated with inflammation and an increase in the levels of biochemical markers of lipid peroxidation. What does this study add? Etanercept exerts a protective effect against lipid peroxidation and improves high‐density lipoprotein antioxidant and anti‐inflammatory properties .